Measuring the work-family integration in organizations - Cachutt Alvarado, Crisdalith (2015)
The objective of this research is to develop an instrument for measuring Work-Family Integration (WFI) and its organizational effect. It is based on a literature review performed above, from which the instrument called WFI Indicators was drawn up. The instrument was applied to a sample of 270 professionals employees of different Venezuelan companies. WFI underlying dimensions were determined, based on the perception of respondents, by analyzing factors (multivariate statistical method), being suitable for the study with a KMO of 0,844. This analysis yielded results in five dimensions for measuring the WFI (WFI satisfaction, commitment, support WFI, Double Presence and health effects), with a total explained variance of 66% and α Cronbach higher than 0.644 for each factor. The results show that the scale obtained is reliable and valid for assessing the components that determine the WFI in organizations.